Efektivitas Penggunaan Google Classroom Dan WhatsApp Dalam Proses Pelaksanaan Belajar Dari Rumah Selama Pandemi Covid-19 Terhadap Hasil Belajar Siswa Di SMA Negeri 4 Sendawar - Ela Septiani; Herliani Herliani; Vandalita M Rambitan (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
This research aims to evaluate the effectiveness of using Google Classroom and WhatsApp in the process of remote learning during the COVID-19 pandemic on students' learning outcomes. The study was conducted at SMA Negeri 4 Sendawar on Munaan Ore Street, Muara Asa, Barong Tongkok District, Kutai Barat Regency, East Kalimantan. The research was carried out for 1 month from August 20th to September 20th, 2021. Purposive sampling technique was used to determine the research sample, resulting in a total of 15 students as samples. Data collection methods included objective tests, interviews, questionnaires, observations, and documentation. The results of the study indicated a significant positive effect of using Google Classroom and WhatsApp on students' learning outcomes in the subject of Biology for Grade XI IPA at SMA Negeri 4 Sendawar, with the calculated t-value > t-table (3.109 > 2.178) at a significance level of 0.05. This implies that the use of Google Classroom and WhatsApp can improve students' learning outcomes in Biology for Grade XI IPA at SMA Negeri 4 Sendawar.